A Study on Printed Multiple Solid Line by Combining Microcontact and Flexographic Printing Process for Microelectronic and Biomedical Applications - Maksud, M. I.; Yusof, M. S.; Abdul Jamil, M. Mahadi (International Journal of Integrated Engineering, 2014)
: Microcontact printing (µCP) is an outstanding surface patterning technique in micron scale and, even in nano scale. Surface science communities like engineers and biologists have been promoting attention in µCP, therefore they have been rich in improvement to the µCP process itself. However the process is relatively slow in production. Meanwhile flexographic technique is a high speed roll to roll process, but low in resolution and still has limitation in printing of micro-scale size. Now a day, low cost fabrication is keys to the successful introduction of printed electronics and roll to roll manufacturing processes. Therefore, study to extend flexographic into the micro-scale size resolutions, may provide an economical commercialization path for electronic devices since, flexographic is a high speed technique commonly used for printing onto very large area flexible substrates. Although low resolution and poor registration are characteristics of today's flexographic process, it has many potential to achieve fine solid line micro size by combining to microcontact printing because both of them having similarities in method of carrying printed pattern to a substrates. This study have been demonstrated that 10micron line with 10micron gap successfully printed by these 2 combinations printing techniques, using graphic ink and biological ink with is Fetal Bovine Serum.